Advanced Nonlinear Control of Single Phase Shunt Active Power Filter Based on Full Bridge Dual Buck Converter. Issue 12 (2022) - Echalih, S.; Abouloifa, A.; Hekss, Z.; Lachkar, I.; Aroudi, A. El; Giri, F.
Abstract: An advanced nonlinear control design of a single phase shunt active power filter based on a full bridge dual buck converter (FBDB-SAPF) is presented in this paper. The main control objectives are: i) compensation of harmonics and reactive power consumed by nonlinear loads aiming at satisfying a near unity power factor at the grid side, ii) regulation of the dc bus voltage to a desired value. To meet the above objectives, the proposed controller has two loops in cascade. The sliding mode approach based on the average state system is used in the inner loop for dealing with the compensation issue and performing PFC. In the outer loop, a filtered proportional-integral is applied to regulate the dc bus voltage of the FBDB-SAPF. The performance of the closed-loop system is tested via Matlab/ SimPowerSystems. The obtained results prove that the suggested controller achieves its objectives and demonstrate its efficiency in terms of tracking and robustness in front of parameter uncertainty.